PENGARUH ISLAMIC CORPORATE GOVERNANCE DAN INTERNAL CONTROL TERHADAP FRAUD PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2016-2020. - Addiarrahman; Khairiyani; Devita Indah Sari (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims determine the effect of Islamic corporate governnace and internlal control on fraud in Islamic comercial banks in Indonesia for the 2016-2020 period. This study uses the independent variable Islamic Corporate Governance by using two indicators, namely the Sharia Supervisory Board and the Board of Directors and Internal Control. While the dependent variable is Fraud. Secondary data is used in this study. This study uses a quantitative approach and uses Panel Data Regression Analysis, Model Testing, Classical Assumption Test, Hypothesis Testing and using the Eviews 8 application. The results of this study show that the Sharia Supervisory Board, Board of Directors and Internal Control have an effect on Fraud . Then the results of the Coefficient of Determination test show that the Adjusted R-square value is 51%, meaning that fraud can be explained by the sharia supervisory board, the board of directors and internal control by 51% and the remaining 40% is explained by other variables. Keywords: Islamic Corporate Governance, Internal Control, Fraud, Islamic Commercial Bank.